ANALISIS KUALITAS PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SALATIGA - Ja'far, M. Hammam; Sulandari, Susi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The Department of Population and Civil Registration of Salatiga City is a government institution that carries out population administration services for the people of Salatiga City. One of its service products is electronic identity card. The electronic identity card service consists of data recording to the printing stages of electronic identity card. The measure used in measuring the quality of service according to Zeithaml (Hardiyansyah, 2011: 42) Quality of service can be measured from 5 dimensions, namely: Tangible, Reliability, Responsivinces, Assurance and Empathy. Factors that affect the quality of service authors use the behavior of officials and communications. There is correlation between apparatus behavior with service quality and communication with service quality. For data analysis use frequency distribution with mean and also included graph. Calculate the correlation of kendall tau using SPSS 17.0 application for apparatus behavior with service quality and communication with service quality. Describe the obstacles experienced during the electronic identity card service process. The conclusion of this study, the quality of electronic identity card service in the Department of Population and Civil Registration of the City of Salatiga as a whole based on the analysis and data processing is good. The correlation of 0,553 means the relationship between apparatus behavior and service quality. The correlation of 0.477 means the relationship between communication and service quality. There are some obstacles in the ministry that is the exhaustion of the blank form of ktp-el. Causing the electronic identity card service is considered low by the community and needs improvement in the level of timeliness of electronic identity card service. The need for information and certainty regarding the electronic identity card service.